Post-COVID-19 Dysphonia: Risk, Voice Handicap, and Laryngological Findings in COVID-19 Critical Illness Survivors - Souza, Juliana Alves; Cielo, Carla Aparecida; Gonçalves, Bruna Franciele da Trindade; Oliveira, Élisson Krug; Lana, Aloma Jacobi Dalla; Pasqualoto, Adriane Shmidt (International Archives of Otorhinolaryngology, 2025)
To investigate and relate the risk of dysphonia, voice handicap, and laryngological findings in COVID-19 critical illness survivors, stratified by sex and the need for orotracheal intubation (OTI) during hospitalization in the intensive care unit. Additionally, identify predictors of voice symptoms after COVID-19 critical illness.A cross-sectional study included 50 patients (mean age 51.70 ± 11.90 years; 26 women and 24 men) from a post-COVID-19 Rehabilitation Outpatient Clinic. Evaluations for voice symptoms and dysphonia risk were conducted using the Screening Index for Voice Disorder, vocal handicap using the Voice Handicap Index, and laryngeal health via laryngoscopic examination.Dysphonia risk and voice handicap were significantly more frequent in women. There was no significant association between voice self-assessment instruments and OTI. However, voice symptoms were significantly higher in intubated women. Commonly reported voice symptoms included dry throat, throat clearing, hoarseness, and vocal fatigue. Intubation was associated with laryngeal disorders, particularly in women, with the hypopharyngeal and supraglottic regions more affected by erythema and edema. Female gender, dyspnea, and cough accounted for 51% of the variance in voice symptoms.COVID-19 critical illness survivors reported dry throat, throat clearing, hoarseness, and vocal fatigue even four months post-discharge. Women were at greater risk of dysphonia and voice handicaps. More than a quarter of patients presented laryngeal disorders related to OTI. Female gender and persistent symptoms of cough and dyspnea were predictors of voice symptoms. These findings enhance understanding of COVID-19's impact on the voice, highlighting the need for multidisciplinary approaches.
Keywords: COVID-19; dysphonia; intensive care units; larynx; voice; voice disorders